Interaction Between Periodontitis and MASLD: Pathophysiological Associations and Possibilities of Prevention and Therapy - Martina Juzbašić; Matej Tomas; Ana Petrović; Marija Hefer; Renata Sikora; Ana Mačković; Stjepan Siber; Martina Smolić (Biomedicines, 2025)
The interrelationship between periodontitis and metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as non-alcoholic fatty liver disease (NAFLD), has attracted increasing attention due to the significant global rise in the prevalence of both conditions. Periodontitis, a chronic inflammatory disease, affects a substantial portion of the population and parallels the growing incidence of MASLD, which currently impacts nearly 30% of the global population. The updated nomenclature reflects a deeper understanding of the condition’s metabolic origins. This narrative review focuses on the shared pathophysiological mechanisms, particularly systemic inflammation, insulin resistance, and oxidative stress that may underlie the bidirectional relationship between these diseases. These mechanisms often act in concert to promote disease development. Unlike previous literature, this review emphasizes the hypothesis that chronic periodontal inflammation may not only mirror but also contribute to the systemic metabolic dysregulation observed in MASLD. We critically assess current evidence supporting this link by highlighting the role of inflammatory mediators in bridging oral and hepatic health, and by proposing an integrated, multidisciplinary approach to its early detection and management. The aim is to offer novel insights that can help develop better prevention strategies and more effective treatments for both diseases.